2015
DOI: 10.1517/13543784.2015.1020370
|View full text |Cite
|
Sign up to set email alerts
|

Investigational therapies targeting signal transducer and activator of transcription 3 for the treatment of cancer

Abstract: Targeting STAT3 activation leads to the inhibition of tumor growth and metastasis both in vitro and in vivo without affecting normal cells; this suggests that STAT3 could be a valid molecular target for cancer therapy. Extensive clinical research is trying to find anti-STAT3 agents with high single-agent activity. The identification and development of novel drugs that can target deregulated STAT3 activation effectively is both a scientific and clinical challenge that needs to be addressed in the near future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 136 publications
0
33
0
Order By: Relevance
“…(11,13). According to the reported studies, STAT3 regulates the transcription of genes involved in cell differentiation, inflammation, proliferation, apoptosis, angiogenesis, metastasis, tumor cell transformation, immune responses, and chemoresistance of tumor cells (11,13,30), which can be a reason for the reduction of cell proliferation and viability in the current study. Also, overexpression of antiapoptotic genes such as Bcl-2 and Bcl-XL is associated with constitutive STAT3 activity.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…(11,13). According to the reported studies, STAT3 regulates the transcription of genes involved in cell differentiation, inflammation, proliferation, apoptosis, angiogenesis, metastasis, tumor cell transformation, immune responses, and chemoresistance of tumor cells (11,13,30), which can be a reason for the reduction of cell proliferation and viability in the current study. Also, overexpression of antiapoptotic genes such as Bcl-2 and Bcl-XL is associated with constitutive STAT3 activity.…”
Section: Discussionmentioning
confidence: 60%
“…Many published data showed that TQ led to the reduction of the number of cytokines including IL-4, IL-5, IL-13, attenuated lipopolysaccharides (LPS)-induced IL-1b, tumor necrosis factor alpha (TNF-a), matrix metalloproteinase (MMP)-13, cyclooxygenase-2, and prostaglandin E 2 (10,29). It is reported that IL-6, due to its receptor, uses many cellular mediators and transducers such as Janus kinase-signal transducers and activators of transcription (JAK-STAT), phosphorylated ERK1/2 (T202/Y204), and phospho-AKT (S473) for its signaling pathways (11,13). In the current study, treatment of PC3 cells with TQ led to the reduction of pAKT, pSTAT3, and ERK1/2 protein signaling pathways (Figure 3), which were in line with those reported in other studies PC3 cell lysates were subjected to SDS-PAGE followed by Western blotting with antiphospho-ERK1/2, anti-phospho-STAT3, and anti-phospho-Akt antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…However, unlike JAKs, STATs are not enzymes, and generating drug candidates suitable for clinical use has been difficult owing to challenges of bioavailability, in vivo efficacy, and selectivity; for instance, STAT3, a heavily investigated target in the treatment of solid-organ malignancy, has a high degree of homology with STAT1. Moreover, STATs represent convergent endpoints for multiple signalling pathways with critical roles in tumour prevention and host defense 123 . These issues must be considered if STATs are to be targeted in the treatment of rheumatic diseases.…”
Section: Targeting Stats?mentioning
confidence: 99%
“…Moreover, recent studies has shown utilization of curcumin in nano formulation and microemulsified forms to increase its bioavailability and site specific action in particular to cancer cells[32, 79,80].Curcumin and its related analogues has also been witnessed to induce epigenetic changes in tumour cells including PC with ability to modulate of histone acetylation by inhibiting histone acetylase [81,82], inducing apoptosis [83], Downregulation of AR and its binding ability [82], regulation of epidermal growth factor receptor(EGFR) tyrosine kinase activity [84,85],inhibition of angiogenesis/vascular endothelial growth factor(VEGF) [86,87], inhibition of cell proliferation in androgen independent and dependent PC cell lines via modulation of Wnt transcriptional activity medicated by low expression of protein in Wnt transcriptional complex [77,[88][89][90][91][92][93].…”
Section: Curcumin (Diferuloylmethane)mentioning
confidence: 99%